INOVASI PELAYANAN PUBLIK “TEMAN KARIB” (TEMUKAN MASALAH IBU HAMIL DENGAN KARTU IBU) DI PUSKESMAS MANNANTI KABUPATEN SINJAI - Regina, Putri; Haerana, Haerana; Hamrun, Hamrun (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2025)
This research aims to determine the Public Service Innovation "Teman Karib" (Find Pregnant Women's Problems with Mother's Cards) at the Mannanti Community Health Center, Tellulimpoe District, Sinjai Regency. This research uses qualitative research. Data collection techniques are through observation, interviews and documentation, data sources come from 10 informants. The results of the research show that the Public Service Innovation "Teman Karib" at the Mannanti Community Health Center has a relative advantage which provides many economic advantages and benefits, suitability shows that this innovation is in accordance with the value of public services, complexity in the innovation there are only a few obstacles, it is possible to try it so far the program The innovation has been tested and proven to have benefits for pregnant women, and is relatively easy to observe because it can be observed by all levels of society.